Epigoitrin, an Alkaloid From Isatis indigotica, Reduces H1N1 Infection in Stress-Induced Susceptible Model in vivo and in vitro - Luo, Zhuo; Liu, Li-Fang; Wang, Xiao-Hua; Li, Wen; Jie, Chong; Chen, Huan; Wei, Fan-Qin; Lu, Dan-Hua; Yan, Chang-Yu; Liu, Bo; Kurihara, Hiroshi; Li, Yi-Fang; et al. (Frontiers in Pharmacology, 2019)
Stress has been proven to modulate an individual’s immune system through the release of pituitary and adrenal hormones such as the catecholamines, growth hormone and glucocorticoids. These signal molecules can significantly alter the host immune system and make it susceptible to viral infection. In this study, we investigate whether epigoitrin, a natural alkaloid from Isatis indigotica, provide a protection against influenza infection by reducing the host’s susceptibility to influenza virus under stress and it’s underlying mechanism. To prove it, mouse restraint stress model and CORT (corticosterone) -induced stress model were employed. Our results demonstrated that epigoitrin significantly decreased the susceptibility of restraint mice to influenza virus, evidenced by lowered mortality, attenuated inflammation and decreased viral replications in lungs. Further results revealed that epigoitrin reduced the protein expression of mitofusin-2 (MFN2), which elevated mitochondria antiviral signaling (MAVS) protein expression and subsequently increased the production of IFN-β and interferon inducible transmembrane 3 (IFITM3), thereby helping to fight viral infections. In conclusion, our study indicated that epigoitrin could reduce the susceptibility to influenza virus via mitochondrial antiviral signaling.